Singular locally scalar representations of quivers in Hilbert spaces and separating functions - Redchuk, I. K.; Roiter, A. V. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
We consider locally scalar representations of extended Dynkin graphs in Hilbert spaces. The relation between these representations and the function ρ( n ) = 1 + ( n − 1 ) / ( n + 1 ) is established. We construct a family of separating functions that generalize the function ρ and play a similar role in a broader class of graphs.